2019
DOI: 10.1186/s13046-019-1418-2
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 3 inhibits glucose metabolism in colorectal cancer by targeting HSP90/STAT3/HK2 signaling

Abstract: BackgroundPolo-like kinase 3 (PLK3) has been documented as a tumor suppressor in several types of malignancies. However, the role of PLK3 in colorectal cancer (CRC) progression and glucose metabolism remains to be known.MethodsThe expression of PLK3 in CRC tissues was determined by immunohistochemistry. Cells proliferation was examined by EdU, CCK-8 and in vivo analyses. Glucose metabolism was assessed by detecting lactate production, glucose uptake, mitochondrial respiration, extracellular acidification rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…The inhibition of STAT3 could suppress the growth of glioma stem cells effectively combined with radiotherapy (27). Besides, it has been reported that STAT3 signaling pathway regulated the expression of HK-2 and PFKL (28,29). In the current study, we found that UBE2D3 knockdown inhibited STAT3 phosphorylation in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…The inhibition of STAT3 could suppress the growth of glioma stem cells effectively combined with radiotherapy (27). Besides, it has been reported that STAT3 signaling pathway regulated the expression of HK-2 and PFKL (28,29). In the current study, we found that UBE2D3 knockdown inhibited STAT3 phosphorylation in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…Given the enrichment of PLK3 at the plasma membrane and Golgi apparatus, it will be interesting to test its potential impact on cell adhesion and intracellular trafficking that are regulated by PP6 phosphatase [48,49]. Finally, there is emerging evidence that expression of PLK3 could affect the therapeutical response in melanoma, prostate cancer and colon carcinoma [50][51][52]. Further phosphoproteomic studies are needed to identify new substrates of PLK3 that could explain its role in cell physiology and sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Serine/threonine protein phosphatase 6 (PP6) is a heterotrimeric complex consisting of the catalytic subunit (PPP6C), SAPS domain-containing subunit (PPP6R1-3) and ankyrin repeat-domain containing regulatory subunit (ANKRD28, 44,52) [24]. PP6 was implicated in cell cycle progression, DNA damage repair, inflammatory signaling, and lymphocyte development [25].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies showed that STAT3 exerts a signi cant effect on the glycolysis and glucose-dependent addiction of tumor cells, which is known as the Warburg effect 16,17 . Speci cally, it has been reported that STAT3 regulates the glucose metabolism through increasing the HK2 expression in cancer cells 18 . Furthermore, STAT3 up-regulates LDHA expression to promote the proliferation of urinary bladder cancer cells 19 .…”
Section: Gsdmb Regulates the Glycolysis Via Activating Stat3 In Bladdmentioning
confidence: 99%